Ritu Shodhana - Way to Stay Healthy with special reference to Virechana (AYUSHDHARA, 2024)
Ayurveda is a unique and ancient science of life which considers the Tridoshas vata, Pitta and Kapha as Tristhunas (pillars) of human body. The aim of Ayurveda is to maintain health of a healthy person and treating ailments of the diseased. Timely elimination of increased Doshas by purificatory measures during specified season is known as Ritu shodhana. Sharadiya Virechana i.e., purification therapy in autumn season is best for elimination of Prakupita (aggravated) Pitta dosha. The present review aims to summarize the benefits of Ritu shodhana with special reference to Virechana on health of a person. Materials and Methods: Literature search was carried out through search engines like PubMed, Web of Science and Google Scholar using keywords like ‘Ritu shodhana’, ‘Virechana’, ‘seasonal regimens’, ‘seasonal variations in India’,’ lifestyle disorders’. Classicals such as Bruhattrayis, Laghuttrayis were also reviewed. The relevant studies were identified and the findings summarized. Result and discussion- Ritu shodhana plays a key role in prevention of diseases. Among Panchakarmas virechana (purgation therapy) is one of the prime purificatory procedures for elimination of Pitta dosha. As the expulsion of Dosha occurs in normal route it is not complicated. Hence it has great promise and requires research in this area.